2021
DOI: 10.1097/jcp.0000000000001492
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Once-Daily Versus Divided Dosing Regimen

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…They found that twice-daily dosing of clozapine theoretically achieved a therapeutic plasma concentration more often than a once-daily dosing regimen. 8 However, similarly to the current study, Kitagawa et al 11 found that the psychiatric symptoms and adverse effects of clozapine did not differ significantly between once-daily and divided dosing regimens. The reason for the effectiveness of once-daily dosing, which was not inferior to divided dosing of clozapine, despite clozapine having a short half-life of 12 hours, may be that there was a slower reduction of central D2 receptor occupancy compared to that observed at antipsychotic blood concentration.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They found that twice-daily dosing of clozapine theoretically achieved a therapeutic plasma concentration more often than a once-daily dosing regimen. 8 However, similarly to the current study, Kitagawa et al 11 found that the psychiatric symptoms and adverse effects of clozapine did not differ significantly between once-daily and divided dosing regimens. The reason for the effectiveness of once-daily dosing, which was not inferior to divided dosing of clozapine, despite clozapine having a short half-life of 12 hours, may be that there was a slower reduction of central D2 receptor occupancy compared to that observed at antipsychotic blood concentration.…”
Section: Discussionsupporting
confidence: 76%
“…These results may be explained by a previous study that found that the peak and trough plasma concentration of clozapine at steady state did not differ significantly between once-daily and divided dosing regimens. 11 Furthermore, this study found that although the median dose of clozapine in the divided dosing group was significantly greater than in the once-daily dosing group, the efficacy was not different between groups. Second, the nonadherence rate was higher in the divided dosing group than in the once-daily dosing group; however, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…1,2 Investigators recently conducted a study to evaluate whether a significant difference in achievable plasma concentration profile exists between the two clozapine dosage regimens, and, if present, whether the difference has implications for the drug's efficacy and toxicity. 3…”
Section: Y W Francis Lam Pharmd Fccpmentioning
confidence: 99%
“…Although clozapine is widely used in patients with treatment‐resistant schizophrenia, there remains relatively little agreement on the comparative effectiveness of once‐ versus multiple‐daily dosing (Kikuchi, et al, 2021; Kitagawa et al, 2022). While the relatively short elimination half‐life of clozapine would seem to favor a multiple‐daily dosing regimen, once‐daily dosing would encourage medication adherence.…”
mentioning
confidence: 99%